2019
DOI: 10.32598/ijmtfm.v9i4.26515
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Patterns of Palmaris Longus Muscle Absence in an Iranian Population

Abstract: Palmaris Longus (PL) is a muscle of the forearm, i.e., not functionally necessary and does not exist in all people. It is a choice for tendon graft and investigating its prevalence is of clinical importance. During April-October 2009, 102 cadavers (78 males, 24 females) were bilaterally necropsied for PL exploration in Zanjan City, Iran. PL Absence (PLA) was observed in 37 (36.3%) cases (28 males, 9 females). PLA prevalence was similar in men (36%) and women (37.5%). Of PLA cases, 19 (51%) were unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…4 A research conducted on cadavers in Iran documented the prevalence to be 36.3%. 12 Similar prevalence was mentioned in a cadaveric study done in Poland. 8 An interesting study conducted in a village in Ukraine revealed that the individuals born before 1945 presented with agenesis prevalence of 70% while the agenesis prevalence decreased by 23% in those who were born after 1945.…”
Section: Introductionsupporting
confidence: 72%
“…4 A research conducted on cadavers in Iran documented the prevalence to be 36.3%. 12 Similar prevalence was mentioned in a cadaveric study done in Poland. 8 An interesting study conducted in a village in Ukraine revealed that the individuals born before 1945 presented with agenesis prevalence of 70% while the agenesis prevalence decreased by 23% in those who were born after 1945.…”
Section: Introductionsupporting
confidence: 72%